Outcomes of Repository Corticotropin Gel for Ocular Sarcoidosis. (18th August 2022) - Oh, Daniel J.; Singh, Arjun; Kanu, Levi N.; Lobo-Chan, Ann-Marie; MacIntosh, Peter W; Bhat, Pooja
ABSTRACT: Purpose: To evaluate the utility and side effect profile of subcutaneous repository corticotropin gel (RCI) in ocular sarcoidosis. Methods: Retrospective chart review. Results: Among six identified patients on RCI therapy, 4 had uveitis, one had optic neuritis and one had uveitis and optic neuritis secondary to sarcoidosis. The average follow-up was 43.5 months. RCI therapy was continuous in 4 patients (average 7.7 months) and intermittent in 2 patients (24 and 12 months). Five of the 6 patients continued with local and/or systemic corticosteroids for ocular inflammation control while on RCI therapy. Two-thirds of patients experienced adverse effects including hyperpigmentation, alopecia, and severe hypertension. RCI therapy was discontinued in 5 of the 6 patients due to continued inflammation and side/adverse effects (4 patients) and loss of follow-up (1 patient). Conclusion: In this small cohort, the majority of patients failed to achieve adequate steroid-sparing ocular inflammation control and experienced side effects while on RCI therapy. Additional studies are needed to elucidate the role of RCI in ocular inflammation.